Effect of Eimeria Infection on Cecal Microbiome of Broilers Fed Essential Oils - Kley, M.A. Martynova-Van; Oviedo-Rondon, E.O.; Dowd, S.E.; Hume, M.; Nalian, A. (International Journal of Poultry Science, 2012)
Coccidiosis causes mucosal damage and predisposes birds to enteropathogen infection. In this study pyrosequencing was used to evaluate effects of coccidiosis on the intestinal microflora of broilers given diets without feed additives or supplemented with either a growth promotant antibiotic and an ionophore, or two essential oil blends. DNA samples were collected from the cecal contents of broilers before (19 d) and after (26 d) infection with mixed Eimeria spp. (E. acervulina, E. maxima and E. tenella). A 454 FLX pyrosequencer and 16S universal primers were used to obtain quantitative profiles of bacterial taxa present in each sample. The relative percent abundance of the identified taxa was analyzed using hierarchical clustering and principal component analysis. Samples from pre-infected broilers were dominated by bacterial species belonging to genera Subdoligranulum, Coprococcus, Alistipes, Lactobacillus and Faecalibacterium. Post-infection samples were dominated by species from the genera Escherichia/Shigella and Bacteroides. Eimeria infection did not significantly affect the richness of the microbial communities but rather its composition. The composition of the cecal microbiome correlated with the average feed conversion ratio. The methodology used in this study proved effective in understanding the effects of coccidia infection on intestinal microflora of broilers raised on diets supplemented with growth promoting antibiotics, ionophores and essential oils.